Alteration of gut microbiota in migraine patients with irritable bowel syndrome in a Chinese Han population - Liu, Jieqiong; Tang, Wenjing; Hou, Lei; Wang, Jing; Wang, Rongfei; Zhang, Yaofen; Dong, Zhao; Liu, Ruozhuo; Yu, Shengyuan (Frontiers in Neurology, 2022)
Objective Migraine is frequently reported in patients with irritable bowel syndrome (IBS), and emerging evidence suggests that gut microbiota plays a role in migraine and IBS. However, alterations in the gut microbiome in migraine patients with IBS remain unknown. This study aimed to explore the compositions of gut microbiota in migraine patients with IBS in a Chinese Han population. Methods Sixteen migraine patients with IBS and thirteen age- and gender-matched IBS patients with similar dietary and lifestyle habits were enrolled in this pilot study. Demographic data, clinical data, eating habits, lifestyle habits, comorbidities, and medications were recorded using a unified case registration form. Questionnaires for the Migraine Disability Assessment (MIDAS), Pittsburgh Sleep Quality Index (PSQI), Hamilton Anxiety Scale (HAMA), and Hamilton Depression Scale (HAMD) were completed. Fecal samples were collected, and microbial DNA was extracted. Gut microbiota 16S ribosomal RNA (16S rRNA) gene sequencing targeting the V4 region was performed using the Illumina HiSeq 2500 high-throughput sequencing platform. The relationships between gut microbiota and clinical characteristics of migraine were analyzed. Results The structure of gut microbiota differed between migraine patients with IBS and patients with IBS, while the richness and diversity of gut microbiota in migraine patients with IBS showed no significant difference from that of patients with IBS. We found a higher relative abundance of the genus Parabacteroides and a lower relative abundance of the genera Paraprevotella, Lachnospiraceae_UCG-010, Lactococcus, Collinsella, and Comamonas in migraine patients with IBS than in patients with IBS. According to random forest predictive models, the phylum Bacteroidota shows the most important role in migraine patients with IBS. Furthermore, no statistical correlation was found between significantly different taxa at the genus level and migraine clinical data. Conclusion This study identified that altered gut microbiota occurred in Chinese Han migraine patients with IBS, but no correlation was found between gut microbiota and the clinical characteristics of migraine. Further study is needed to better understand the role of gut microbiota in the pathogenesis of migraine in IBS.